Aktuelle Herausforderungen der Wettbewerbspolitik durch Marktplätze im Internet - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2016)
– This essay discusses two immanent challenges for competition policy in online e-commerce markets: the platform character and the role of personalized data. Both phenomena are briefly described from an economic perspective (section 2 and 3) with a focus on how they affect and change competition and markets. Section 4 summarizes landmark antitrust cases and current antitrust concerns re-garding electronic marketplaces like Facebook, Google, or Amazon. Based upon the state of economic theory and the observed patterns of behavior in the landmark cases, implications for competition policy are derived. The essay argues that mo-nopolization and abuse of dominance will be the most relevant areas of competi-tion policy in e-commerce markets, inter alia, due to a naturally more narrow mar-ket structure. Furthermore, abusive strategies may come in a very different shape than on traditional markets. In particular, competition authorities and rules should not only focus on monetary transactions since data plays an important role and may serve as an instrument to exploit consumers or deter competitors. In general, an active competition policy is recommendable in order to keep markets open for further competition and innovation dynamics. Special, more far-reaching regulation beyond the application of an e-commerce-adapted competition policy, however, is not recommendable from an economic perspective and must be expected to do more harm than good.
Keywords: L40; K21; L81; L82; L86; L13; 330; competition policy; internet economy; e-commerce; platform economics; economics of privacy; big data; personalized data; antitrust; Google; Amazon; Facebook